A Commentary on Peace and Conflict in Latin America Since 2020 - Aparaajita Pandey, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
The Latin American region displays an unnerving nonchalance about the rates of crime, history of violence, present and persisting racial divide, corruption in the government, sprawling narcoterrorism, and widening income and gender gap. While these are not unheard of in other parts of the world, their combined presence and a general lack of forceful resistance in the past is symptomatic of the colonial past and its legacies that Latin America still grapples with on a sociopolitical and economic level. However, the pandemic has stretched the region to its limits and as a new generation becomes a part of the workforce, protests for political change have become commonplace. As the region is in the midst of a transformation, understanding the birth and potential for conflict, both traditional and non – traditional in the region becomes imperative for its study. Taking cues from the above, this article attempts to explore, understand, and recognize cycles of peace and conflict in the region of Latin America.